Beta-amyloid short- and long-term synaptic entanglement. (January 2019) - Lanni, Cristina; Fagiani, Francesca; Racchi, Marco; Preda, Stefania; Pascale, Alessia; Grilli, Massimo; Allegri, Nicola; Govoni, Stefano
Graphical abstract: Abstract: Beta-amyloid (Aβ) is a peptide that derives from the proteolytic cleavage of the amyloid precursor protein (APP) by several secretases. Since its isolation and sequencing from Alzheimer's disease (AD) brains, Aβ has been intensively investigated in the context of AD as the main pathogenic marker responsible for neurodegenerative processes. During the last three decades, results from several independent studies have converged to form the so-called amyloid cascade hypothesis of AD and several therapeutic strategies designed to modulate the APP amyloidogenic pathway have been developed. However, none of the clinical trials targeting Aβ culminated in a significant clinical outcome, thus challenging the concept that targeting Aβ, at least within the time window so far explored in clinical trials, may have a therapeutic effect. However, besides its presence in AD brains, brain cells produce Aβ, thus suggesting that, under normal conditions, the peptide may have a role in the regulation of brain functions, which is consistent with its ubiquitous presence and normal synthesis. Taking into account that Aβ has been found to exhibit a dual role strictly correlated with its concentration (neuromodulatory/neuroprotective vs neurotoxic), we discuss emerging evidence indicating that physiological concentrations of Aβ peptide modulate synaptic activity. The review examines the physiological effects of Aβ on acute synaptic activities and the functional interplay existing between Aβ and different neurotransmitter systems, i.e. cholinergic, glutamatergic, GABAergic, catecholaminergic, serotoninergic, and peptidergic. The review also provides an insight into the different mechanisms through which Aβ affects synaptic activity, focusing in particular on Aβ interaction with the key synaptic proteins that regulate the neurotransmitter release machinery. These interactions may help to identify or recognize alterations in neurotransmitter activity and correlated behaviors as predictive signs for the development of AD and to understand the limitations of current interventions and the failure so far of amyloid targeted therapies.